Clinical update on sensorineural hearing loss in Turner syndrome and the X‐chromosome. Issue 1 (10th January 2019) - Bonnard, Åsa; Bark, Rusana; Hederstierna, Christina
Abstract : Hearing loss is one of the major medical concerns in girls and women with Turner syndrome (TS) and has a negative effect on well‐being and quality of everyday life. Sensorineural hearing loss is the most common type of hearing loss, affecting more than half of adults with TS. Karyotypes with a loss of the short p‐arm on the X‐chromosome are more prone to ear and hearing problems. The importance of detecting, investigating, and treating hearing loss with hearing aids cannot be emphasized enough. The pathophysiology of the sensorineural hearing loss in TS is not known, but theories regarding estrogen deficiency, the cell cycle delay hypothesis, IGF‐1 deficiency and the possible role of the KDM6A gene are discussed. Due to the diversity of symptoms and conditions within the same karyotype, a combination of genetic factors altered by epigenetic and/or hormonal effects is probable. Further research is needed regarding the pathophysiology of ear and hearing problems in TS to develop new treatment methods.